2021
DOI: 10.1038/s41598-021-89450-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural genomics approach to investigate deleterious impact of nsSNPs in conserved telomere maintenance component 1

Abstract: Conserved telomere maintenance component 1 (CTC1) is an important component of the CST (CTC1-STN1-TEN1) complex, involved in maintaining the stability of telomeric DNA. Several non-synonymous single-nucleotide polymorphisms (nsSNPs) in CTC1 have been reported to cause Coats plus syndrome and Dyskeratosis congenital diseases. Here, we have performed sequence and structure analyses of nsSNPs of CTC1 using state-of-the-art computational methods. The structure-based study focuses on the C-terminal OB-fold region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…If a mutation is shown destabilizing by four out of the five tools, we have considered that as a destabilizing mutation. A detailed protocol of structure-based mutational analyses can be found in our previous reports ( Amir et al., 2019 ; Mohammad et al., 2020 ; Choudhury et al., 2021 ; Habib et al., 2021 ; Umair et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…If a mutation is shown destabilizing by four out of the five tools, we have considered that as a destabilizing mutation. A detailed protocol of structure-based mutational analyses can be found in our previous reports ( Amir et al., 2019 ; Mohammad et al., 2020 ; Choudhury et al., 2021 ; Habib et al., 2021 ; Umair et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies on mutant protein–ligand complexes have produced similar results with the analysis of RMSD, H-bonds, and SASA [ 69 , 70 , 71 , 72 ]. It was also observed that the fluctuation was high for the 0–125 ns simulation compared to the 150–250 ns simulation for these three analyses, specifically for RMSD ( Figure 8 A2,B2,C2).…”
Section: Discussionmentioning
confidence: 69%
“…PARK7 acts as both a causative and carcinogenic gene and plays a crucial role in oxidative stress [10]. Because mutations in PARK7 cause various complex diseases, we studied several variants of PARK7 using state-of-the-art computational approaches [12][13][14][15][16]. We took 152 mutations of the whole protein to explore their consequences in disease progression.…”
Section: Introductionmentioning
confidence: 99%